The origins of German self-cultivation : Bildung and the future of the humanities - Ham, Jennifer, 1956-; Kinzel, Ulrich, 1956-; Pan, David, 1963- (New York : Berghahn Books, 2023)
"Recent devaluations of a liberal arts education call the formative concept of Bildung, a defining model of self-cultivation rooted in 18th and 19th century German philosophy and culture, into question and force us to reconsider what it once meant and now means to be an "educated" individual. This volume uses an arc of interdisciplinary scholarship to map both the epistemological origins and cultural expressions of the pivotal notion of Bildung at the heart of pursuit in the humanities. From its intriguing original historical manifestations to its continuing resonance in current ongoing debates surrounding the humanities, the editors urge us to ask and discover how the classical concept of Bildung, so central to humanistic inquiry, was historically imagined and applied in its original German context"--
Chapter 5 -- From Bildungsmaschine to Willenserziehung: Nietzsche's Project of Heroic Minds -- Chapter 6 -- The Self-Formation of Poetic Expression: Wilhelm Dilthey's Geistesgeschichte -- Chapter 7 -- Bildung as Dialectical and Theological Hermeneutics in the Service of the Humanities -- Conclusion -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 15, 2023).
JSTOR
Keywords: Education -- Germany -- Philosophy -- History -- 18th century; Education -- Germany -- Philosophy -- History -- 19th century; Education, Humanistic -- Germany -- History -- 18th century; Education, Humanistic -- Germany -- History -- 19th century; Germany -- Identity (Philosophical concept); Germany -- National characteristics; Éducation -- Allemagne -- Philosophie -- Histoire -- 18e siècle.; Éducation -- Allemagne -- Philosophie -- Histoire -- 19e siècle.; Éducation humaniste -- Allemagne -- Histoire -- 18e siècle.; Éducation humaniste -- Allemagne -- Histoire -- 19e siècle.; HISTORY / Europe / Germany; National characteristics; Education, Humanistic; Education -- Philosophy; Identity (Philosophical concept); Germany; 1700-1899; Electronic books; History